El proyecto educativo institucional y el desarrollo académico y administrativo, de la Escuela Fiscal Mixta Ciudad de Loja, de la parroquia El Sagrario, del cantón y provincia de Loja, en el período 2011-2012 - Muñoz Torres, Carmen Rocío (2013)
Any educational organization should clarify its vision, mission and purpose, and these intentions must be possessions in the minds of all persons and estates within it. This research aims to determine the influence of Institutional Education Project on Academic and administrative school Loja City. The methods used were: Deductive, Inductive and Analytical, which allowed them to know the reality of the issues raised, get the relevant information and content, the techniques used were: Steering interview, surveys applied to teachers and parents of the school, and guidance documents. The results concluded that there is little participation in the development of diagnostics for Institutional Educational Project construction, therefore the mission is designed to define the image negative institutional management performed by the management is poor in generating specific projects implementation and change in academic development, the code of coexistence, has insufficient commitments to improve the working environment in the institution, as well as the rules of procedure established arrests the establishment and institutional strengthening.